EVALUASI MUTU DAN ANALISIS USAHA SUSU KEDELAI (Glicine max L. Merr) KEMASAN PLASTIK DI BANDAR LAMPUNG - Prayuga, Nur; Hanum, Tirza; Rangga, Azhari (Teknologi Hasil Pertanian Fakultas Pertanian Universitas Lampung, 2014)
The purposes of this study were to determine the quality diversity of plastic- packed Â soy milk sold in Bandar Lampung, and business analysis of production of soy milk plastic package.Â The data of soy milk quality were collected from 8 vendors and 6 producers which determined using purposive sampling method.Â The data were tested using ANOVA and continued tested using Duncan multiple range test.Â The business analysis were discussed descriptively.Â The results showed that the quality of soy milk packed in a plastic bag sold by different vendors were significantly different. The Â protein contents ranged from 0,78 â 2,58% w/w; pHÂ 6,32 â 6,78; total solid 10,10 â 15,98% w/w, and total microbial content Â 5,07 â 5,70 log CFU/ml. The colors ranging from yellowish white â brownish white; the overall acceptance ranged from neutral âlike; taste ranged from less sweet â sweet, and Â the flavor of soy milk samples were not different which wasÂ described asÂ as slightly unpleasant.Â The business analysis of soy milk packed in a plastic bag which had Â NPV = Rp 40.079.472,73; B/C = 1,38; IRR = 485,72%; Pb = 0,21; BEP of fix cost = 711,74; and Production of BEP = 114, showed that the businesses are profitable and proper to be developed (NPV > 0, B/C ratio > 1, IRR > discount factor 11.00%, payback period < the economic period (4 years), fix cost > BEP of fix cost, and total production > production of BEP). Keywords : business analysis, milk, quality evaluation, soybean